The difference in the comparative research on the example of the project "Cultural education of adults in Poland and Germany" - Sylwia Słowińska; Hanna Solarczyk-Szwec (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
The subject of the reflection is the role of difference and the approach to it in conceptualization and conduct comparative research of adult education on the example of the project "Cultural education of adults in Poland and Germany" which was executed in years 2000-2003. After 15 years we look at the cultural education of adults in Poland once again in order to determine the dynamics of the differences on the examined area through the prism of the continued research. In the conclusion we refer to what can be the added value of comparative research.